Download presentation
Presentation is loading. Please wait.
Published byThomas Sharp Modified over 9 years ago
1
+ Completing the Square and Vertex Form
2
+ Completing the Square
3
+ Perfect Square Trinomials Quadratic Trinomials with a repeated factor! X 2 + 10x + 25 X 2 – 16x + 64 X 2 + 18x + 81
4
+ Solving a Perfect Square Trinomial We can solve a Perfect Square Trinomial using square roots. X 2 + 10x + 25 = 36
5
+ Solving a Perfect Square Trinomial X 2 – 14x + 49 = 81
6
+ What if it’s not a Perfect Square Trinomials?! If an equation is NOT a perfect square Trinomial, we can use a method called COMPLETING THE SQUARE.
7
+ Completing the Square Using the formula for completing the square, turn each trinomial into a perfect square trinomial.
8
+ Solving by Competing the Square Solve by completing the square: X 2 + 6x + 8 = 0
9
+ Solving by Competing the Square Solve by completing the square: X 2 – 12x + 5 = 0
10
+ Solving by Competing the Square Solve by completing the square: X 2 – 8x + 36 = 0
11
+ Vertex Form
12
+ Standard form vertex
13
+ Vertex Vertex: highest or lowest point on the graph. 2 ways to find Vertex: 1) Calculator: 2 nd CALC MIN or MAX 2) Algebraically
14
+ Find the Vertex 1) x 2 + 8x + 1 2) x 2 + 2x – 5 3) 2x 2 – 10x + 3
15
+ Complete the Square Investigation Step 1: Complete the square: X 2 + 4x – 4 = 0 Step 2: DON’T SOLVE! Instead get zero on one side. Step 3: graph the non-zero side and find the vertex
16
+ Completing the Square Finds the vertex! Use completing the square to find the vertex of each: 1) x 2 + 6x + 8 = 0 2) X 2 – 2x + 10 = 0
17
+ Vertex Form
18
+ Converting from Standard to Vertex Standard: y = ax 2 + bx + c Things you will need: a = and Vertex: Vertex: y = a(x – h) 2 + k
19
+ Example Convert from standard form to vertex form. y = -3x 2 + 12x + 5
20
+ Example Convert from standard form to vertex form. y = x 2 + 2x + 5
21
+ Now Convert and Solve Convert each quadratic from standard to vertex form. Then Solve for x. 1. x 2 + 6x – 5 = 0
22
+ Now Convert and Solve Convert each quadratic from standard to vertex form. 1. 3x 2 – 12x + 7 = 0 2. -2x 2 + 4x – 3 = 0
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.